Interval follow up of a 4-day pilot program to implement the WHO surgical safety checklist at a Congolese hospital - Michelle C. White; Jennifer Peterschmidt; James Callahan; J. Edward Fitzgerald; Kristin L. Close (BMC, 2017)
Abstract Background The World Health Organisation Surgical Safety Checklist (SSC) improves surgical outcomes and the research question is no longer 'does the SSC work?' but, 'how to make the SSC work?' Evidence for implementation strategies in low-income countries is sparse and existing strategies are heavily based on long-term external support. Short but effective implementation programs are required if widespread scale up is to be achieved. We designed and delivered a four-day pilot SSC training course at a single hospital centre in the Republic of Congo, and evaluated the implementation after one year. We hypothesised that participants would still be using the checklist over 50% of the time. Method We taught the four-day SSC training course at Dolisie hospital in February 2014, and undertook a mixed methods impact evaluation based on the Kirkpatrick model in May 2015. SSC implementation was evaluated using self-reported questionnaire with a 3 point Likert scale to assess six key process measures. Learning, behaviour, organisational change and facilitators and inhibitors to change were evaluated with questionnaires, interviews and focus group discussion. Results Seventeen individuals participated in the training and seven (40%) were available for impact evaluation at 15 months. No participant had used the SSC prior to training. Over half the participants were following the six processes measures always or most of the time: confirmation of patient identity and the surgical procedure (57%), assessment of difficult intubation risk (72%), assessment of the risk of major blood loss (86%), antibiotic prophylaxis given before skin incision (86%), use of a pulse oximeter (86%), and counting sponges and instruments (71%). All participants reported positive improvements in teamwork, organisation and safe anesthesia. Most participants reported they worked in helpful, supportive and respectful atmosphere; and could speak up if they saw something that might harm a patient. However, less than half felt able to challenge those in authority. Conclusion Our study demonstrates that a 4-day pilot course for SSC implementation resulted in over 50% of participants using the SSC at 15 months, positive changes in learning, behaviour and organisational change, but less impact on hierarchical culture. The next step is to test our novel implementation strategy in a larger hospital setting.